Mechanical properties of CAD/CAM polylactic acid as a material for interim restoration. Issue 4 (April 2023) - Choi, Won-Il; Yoo, Lee-gang; Kim, Yu-ri; Jung, Bock-Young
Abstract: Statement of problem: Biomaterials, including polymethyl methacrylate (PMMA) and bisacrylate, have been widely used as conventional interim materials and may exhibit cytotoxicity or systemic toxicity. Purpose: This study was designed to compare the mechanical properties of polylactic acid (PLA) as an alternative to conventional dental polymers for computer-aided design and manufacturing (CAD/CAM). Material and methods: Four groups (n = 20 per group) of CAD/CAM polymers were assessed. Specimens of PLA (PLA Mill) and PMMA (PMMA Mill) for subtractive manufacturing, PLA for fused deposition modeling (PLA FDM), and bisphenol for additive manufacturing by stereolithography (Bisphenol SLA) were fabricated into 2-mm-wide, 2-mm-thick and 25-mm-long specimens using a milling machine, an FDM printer, and an SLA printer, respectively. The flexural strength (FS) and elastic modulus (EM) were calculated. The surface roughness and Shore D hardness were analyzed with a 3D optical surface roughness analyzer and a Shore durometer, respectively. Results: PLA Mill showed the lowest FS (64.9 ± 8.28), followed by PLA FDM (104.27 ± 4.42 MPa), PMMA Mill (139.2 ± 20.95 MPa), and Bisphenol SLA (171.56 ± 15.38 MPa), with statistically significant differences. PLA FDM showed the highest EM, followed by PLA Mill, Bisphenol SLA, and PMMA Mill. Significant differences were observed not only between PMMA Mill and Bisphenol SLA but also between PLA FDM and PLA Mill. The lowest Shore D hardness was observed for PLA FDM, followed by PLA Mill, PMMA Mill, and Bisphenol SLA, which showed the highest value among the 4 groups, with significance. The highest values for the surface roughness parameters were observed for PLA Mill, and the lowest were observed for Bisphenol SLA. Conclusions: Among the tested CAD/CAM polymers, Bisphenol SLA was the most durable material, and the mechanical properties of PLA FDM were within the clinically acceptable range.